Atributos biológicos e físicos do solo com o uso de biofertilizante - Bertollo, Gilvan Moisés (2015)
The use of biofertilizers has been effective alternative to proper disposal of waste. However, addition of organic waste culture systems can influence the soil biota, microorganisms, and the physical properties of the soil. The objective of this study was to determine the influence of biofertilizer application in fauna and soil physical properties. The study was conducted in four experiments. The first consisted of the evaluation of soil fauna with the use of biofertilizers bovine in a randomized design with factorial arrangement 5 x 12, five fertilization (0 (no biofertilizer control), 150, 300, 450 and 600 L ha-1 biofertilizer bovine), twelve months, with four replications. The second study was analyzed the multiplication of springtails in laboratory conditions under different crop residues and doses of bovine biofertilizer. Another experiment was conducted to evaluate the microbiological changes in soil submitted to fertilization with bovine biofertilizer with randomized block experimental design and, finally, we evaluated the physical properties of an Oxisol submitted to doses of bovine biofertilizer. It was observed that the bovine biofertilizer not interfere in the analyzed biological variables and for the orders, all varied over the time of collection except for Lepidoptera. In reproduction of Collembola laboratory, bovine biofertilizer favors until the estimated dose of 266 L ha-1 and crop residues tested without the use of yeast favors the proliferation of Collembola. The activity of soil organisms is greater on the surface and the estimated dose of 298 L ha-1 bovine biofertilizer and the application of bovine biofertilizer only enabled the rise of evidence macroporosity and microporosity decreased when used doses up to 268 and 293 L ha-1, respectively, necessitating further studies to confirm these results.